Media’s Role in E-Waste Awareness - A Perspective of Rural and Urban Population of Maharashtra - Viraja Bhat, Ojas Savale, (International Journal of Modern Agriculture, 2020)
Electronic devices have been one of the essential part of every individual across the globe due to the digital connect and requires contemporary electronic devices. Along with developed nations, India though being developing having an edge in the software services together with a demographic advantage having a population of 1.3 billion is also the second largest market of consumer electronics in the world. Increase use of electronic devices in Indian households has also led to a new stream of waste – e waste which gets generated by end of life electronic devices after their useful lifespan. Technological advancements and economies of scale of manufacturing electronic devices have been within the scope of all sections of society which has been reason for producing enormous amount of e waste. Usage of electronic devices has been considerable in rural areas, catching up with the urban areas and contribute in e waste generation. Current deteriorating solid waste management scenario in urban and rural areas have been of concern due to addition of e-waste. User awareness and medias role play an important role in management of e-waste in urban and rural areas. The authors in this paper have carried out a comparative study through a primary survey method with a structured questionnaire and field visits in Pune, a metropolitan city and Pandharpur, rural town in Maharashtra to understand the e-waste management scenario.